Degradation of Pesticide Residues Cherizeb and Emacel in Chili Washing Water using ZnO/Zeolite Catalyst through Photolysis - Zilfa; Safni; Benny Damas Putra (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Chili (Capsicum annuum L) ) is one of the most important horticultural commodities widely consumed in Indonesia and has high economic value. To maintain productivity and prevent pest attacks, farmers commonly apply chemical pesticides intensively. However, excessive and improper pesticide application can leave harmful residues on the surface and within the tissues of chili fruits. The accumulation of these residues not only poses health risks to consumers but also contributes to environmental pollution, particularly in wastewater generated from chili washing activities. This study aims to reduce pesticide residues of Cherizeb and Emacel in chili washing water using the photolysis methodassisted by a ZnO/zeolite catalyst. Zinc oxide (ZnO) acts as a photocatalyst activated by ultraviolet (UV) light to produce reactive hydroxyl radicals (•OH) capable of decomposing complex organic compounds into simpler compounds such as CO₂ and H₂O. Meanwhile, zeolite is used as a catalyst support due to its large surface area and high adsorption capacity, allowing adsorption and photocatalytic processes to occur simultaneously. The results showed that the photolysis method using the ZnO/zeolite catalyst significantly reduced pesticide residues, with optimum degradation efficiencies of 85.66% for Cherizeb using 0.8 g ZnO/zeolite under UV irradiation for 60 minutes, and 83.97% for Emacel using 0.8 g ZnO/zeolite under UV irradiation for 75 minutes. The samples were characterized using Fourier Transform Infrared Spectroscopy (FTIR) to identify functional groups, indicating the disappearance of specific organic functional groups. Pesticide residues on chili samples were analyzed using UV-Vis spectrophotometry to determine concentrations before and after treatment. X-Ray Diffraction (XRD) analysis confirmed that the crystalline structure of the catalyst remained stable after the photolysis process. Based on these findings, the ZnO/zeolite catalyst is proven to be effective in reducing pesticide residues through photocatalytic degradation and has the potential to be applied as a safe, efficient, and environmentally friendly post-harvest technology to improve the quality of agricultural products.